Diverse employment challenges in Indonesia: Finding solutions for the future - Rizki Ananda, Azzahra; Dwiono, Sugeng (Journal of Law Science, 2024)
As of February 2022, the open unemployment rate (TPT) in Indonesia was 5.83%, a decrease from February 2021. The workforce was composed of 144.1 million people, with 11.53 million unemployed, or 5.53%. The COVID-19 pandemic impacted various groups within the working-age population: 0.96 million were directly unemployed due to COVID-19, 0.55 million left the labor force, 58 million were not working, and 44 million were at risk of unemployment. The Republic of Indonesia Law No. 13 of 2003 defines employment, and Sumarsono (2003) describes labor as those willing to work. Indonesia's population reached approximately 275.77 million in 2022, a growth of 5.57 million since 2020, increasing the workforce and unemployment rate. The low quality of labor in Indonesia, attributed to inadequate education, has an impact on workers' skills, knowledge, and technological proficiency, affecting their earnings. There is a misalignment between graduates' skills and industry needs, and challenges exist in matching competencies with job market demands.